Infestação de Diatraea saccharalis em cultivares de cana-de-açúcar - Link, Dionisio; Costa, Ervandil Correa; Dariva, Thelmo; Silva, Maria Isabel da (Revista do Centro de Ciências Rurais, 2008)
Estudou-se a intensidade de infestação da broca da cana-de-açúcar, Diatraea saccharalis (Fabricius, 1794), em 14 cultivares de cana-de-açúcar introduzidas em Santa Maria, RS, em dois cortes bi-anuais. A intensidade de infestação variou de 0, 17 a 3, 82% e de 1,19 a 12,38% dos internódios brocados nos dois cortes. As cultivares CB-56-121 e CB-40-69 foram as mais infestadas nos dois cortes, enquanto as cultivares CB-56-126, IAC-50-134 e IAC-54-439 sofreram os menores índices de infestação. Abstract The intensity of infestation of the sugar cane borer Diatraea saccharalis (Fab., 1794) was studied in fourteen varieties, during two harvest-years in Santa Maria, RS, Brazil. The intensity of infestation varied between 0.17 and 3.82% and between 1.19 and 12.38% at the first and second harvesting years respectively. The varieties CB-56-121 and CB-40-69 were the most infested at both harvests, whereas the cultivars CB-56-126, IAC-50-134 and IAC-54-439 were the least infested.